Comparison of selective plasma exchange and plasmadialfiltration with MARS and Prometheus systems in the treatment of liver failure - A. A. Sokolov; S. I. Rey; I. V. Aleksandrova; A. V. Popov; L. L. Gendel; S. N. Gubanova; L. V. Marchenkova; M. V. Sudakov (Вестник анестезиологии и реаниматологии)
The mortality of patients with hepatic failure remains high. Often the patient's life can be saved only with extracorporeal liver support (ELS). ELS systems – MARS® и Prometheus® have proved their efficacy but their widespread use is constrained by their very high cost. Introduction in clinical practice of new affordable ELS systems is a topical issue. The objective: to compare clinical and laboratory effects of selective plasma exchange (SPE), plasmadialfiltration (PDF) with use of the selective membrane plasma separators EvaclioTM and MARS® and Prometheus® (FPSA) systems in the treatment of liver failure. Subjects and methods: 15 extracorporeal procedures of each type were performed in 52 patients with acute liver failure (14) and acute-on-chronic liver failure (38): MARS, FPSA, PDF, SPE with use of Evaclio ЕС-2C, and ЕС-3C, ЕС-4C. The clinical and laboratory parameters (total, direct and indirect bilirubin, total protein, albumin, creatinine, urea, etc.), severity of the condition according to MELD score were determined before and after the session and the next morning. Changes, side effects and complications of procedures were assessed and compared. Results. Reduction of concentration of direct bilirubin was comparable with FPSA, PDF and SPE on Evaclio ЕС-3C20 и ЕС-4C20 (38-42%), indirect bilirubin – with PDF and SPE on Evaclio ЕС-3C20 и ЕС-4C20 (29-34%). Low-molecular metabolites (urea, creatinine) were better removed with FPSA (35-44%) and PDF (40-42%). The reduction of their concentration with SPE was insignificant. The reduction of albumin level was the highest with FPSA (10.2%) and SPE on Evaclio ЕС-4C20 (14.3%). All investigated ELS methods did not exert a significant influence on the basic parameters of blood coagulation and quantity of blood cells. No side effects and complications were observed. Conclusion: Selective plasma exchange and plasmadiafiltration are generally comparable in clinical and laboratory effects in the treatment of liver failure with MARS and Prometheus system provided significantly lower costs.